Lethal and sublethal effects of cadmium in the white shrimp Palaemonetes argentinus: A comparison between populations from contaminated and reference sites - Chiodi Boudet, Leila Natalia (2013)
In the present study, the acute toxicity of cadmium (Cd) in white shrimp (Palaemonetes argentinus) from a metal polluted lagoon (Los Padres, LP) and from unpolluted lagoon (Nahuel Ruca, NR) was evaluated. Both population, were exposed to 3.06, 12.26, 30.66, 61.32, 306 and 613.2 mg Cd L1 for 96-h. The sublethal effects of Cd were examined by two cellular biomarkers: metallothionein (MT) and lipid peroxidation (LPO). The seasonal variations of biomarkers in both lagoons were also evaluated. P. argentinus demonstrated a high sensitivity to Cd, with values of 96-h LC50 lower and close to those of highly sensitive species; therefore, can be proposed as a good indicator species. The LC50 values of shrimp from LP (24-h: 269.8, 48-h: 67.45, 72-h: 30.66, 96-h: 24.50 mg Cd L1 ) were higher than those from NR (24-h: 153.3, 48-h: 32.65, 72-h: 18.40, 96-h: 12.26 mg Cd L1 ), indicating a higher tolerance to Cd, and it was related to their origin. Differential responses in terms of MT induction and LPO between populations were also detected. In NR shrimps, the MT synthesis was induced very fast (24-h) and even at the minimum concentration tested (3.06 mg Cd L1 ), while no increases were observed in LPO levels. In contrast, the MT and LPO levels in LP shrimps were not increased relative to control, although they were more tolerant to Cd than those of NR; suggesting the presence of another mechanism involved in the detoxification of Cd. The differences in both sensitivity and biochemical responses to Cd may be related with their environmental histories.